Increased CD40 Ligation and Reduced BCR Signalling Leads to Higher IL-10 Production in B Cells From Tolerant Kidney Transplant Patients. Issue 3 (March 2017) - Nova-Lamperti, Estefania; Chana, Prabhjoat; Mobillo, Paula; Runglall, Manohursingh; Kamra, Yogesh; McGregor, Reuben; Lord, Graham M.; Lechler, Robert I.; Lombardi, Giovanna; Hernandez-Fuentes, Maria P.
Abstract : Background: An increased percentage of peripheral transitional B cells producing IL-10 has been observed in patients tolerant to kidney allografts. In healthy volunteers, the balance between the CD40 and B-cell receptor (BCR) signalling modulated IL-10 production by B cells, with stimulation via the BCR decreasing CD40-mediated IL-10 production. In this study, we evaluate whether in tolerant kidney transplant patients, the increased IL-10 production by B cells was due to an altered CD40 and/or BCR signalling. Methods: B cells obtained from a new cohort of tolerant renal transplant recipients and those from age- and sex-matched healthy volunteers were activated via CD40 and BCR, either alone or in combination. Results: In tolerant patients, we observed higher percentages of B cells producing IL-10 after CD40 ligation and higher expression of CD40L on activated T cells compared with healthy controls. Furthermore, B cells from tolerant recipients had reduced extracellular signal-regulated kinase signalling after BCR-mediated activation compared with healthy controls. In keeping with this, combining BCR signalling with CD40 ligation did not reduce IL-10 secretion as was observed in healthy control transitional B cells. Conclusions: Altogether, our data suggest that the altered response of B cells in tolerant recipients may contribute to long-term stable graft acceptance. Abstract : Nova-Lamperti and colleagues report that compared to transitional B cells from healthy volunteers, transitional B cells from tolerant patients produce more IL-10 following CD40-ligation, exhibit reduced ERK-phosphorylation following BCR-engagement and are more resistant to BCR-mediated suppression of CD40-induced IL-10 production. Supplemental digital content is available in the text.